The spirituality of the Letter to the Galatians - D. F. Tolmie (Acta Theologica)
The spirituality of the Letter to the Galatians has not received much attention so far. Accordingly, this issue is addressed in this article. After a brief overview of two studies that have already been done in this regard, the focus of this investigation is formulated as the spirituality that comes to expression in the Letter to the Galatians. Of the different approaches available to investigate this matter, the approach of Kees Waaijman is selected. In terms of this approach, two issues are then investigated systematically, namely the divine-human relational process as reflected in the Letter to the Galatians and the transformation process as reflected in the Letter.